Case Report: First case of West Nile virus meningoencephalitis in Southwest Michigan in a patient on ixekizumab and prednisone - Zou, Henry; Elzalabany, Sara; Kenyon, Ingrid; Kelly, Matthew (Frontiers in Medicine, 2026)
BackgroundMeningoencephalitis involves inflammation of the meninges and brain parenchyma and is commonly associated with bacterial or viral infection. West Nile virus (WNV) is a mosquito-borne, single-stranded RNA arbovirus that rarely induces neuroinvasive disease. We present the first case of West Nile meningoencephalitis in Southwest Michigan.Case reportA 58-years-old male with cardiovascular disease, chronic obstructive pulmonary disease, diabetes, chronic kidney disease and psoriasis presented with chest pain, dyspnea, and confusion. Brain imaging was negative, but he developed worsening weakness, nausea, vomiting, fever, and confusion. He received mosquito and tick bites 2 weeks prior. He was started on empiric antibiotic and antiviral therapy and subsequently developed a diffuse morbilliform rash. Initial infectious workup and lumbar puncture were negative, and he was transitioned to solely supportive care. He was discharged after 11 inpatient days following symptomatic improvement, and 6 days later his cerebrospinal fluid was positive for West Nile virus.SignificanceWest Nile virus is the most common source of mosquito-borne disease in the mainland USA but <1% present as neuroinvasive disease. Supportive care is the mainstay of treatment, though multiple therapies are under investigation. Our patient’s immunosuppressing medications and multiple comorbidities placed him at greater risk of developing West Nile meningoencephalitis.